Synthesis of a Layered Organic-Inorganic Nanohybrid of 4-Chlorophenoxyacetate-zinc-Layered Hydroxide with Sustained Release Properties. (18th December 2011) - Hussein, Mohd Zobir; Nazarudin, Nor Farhana binti; Sarijo, Siti Halimah; Yarmo, Mohd Ambar
Abstract : A zinc-layered hydroxide-4-chlorophenoxy acetate (4CPA) organic-inorganic nanohybrid was prepared using a simple direct reaction of 4CPA anions with ZnO under an aqueous environment to be used as a controlled release formulation of the herbicide, 4CPA. The concentration of the active agent, 4CPA, was found to be a controlling factor for the formation of a pure phase well-ordered nanolayered hybrid in which it could be synthesised at 0.2 M 4CPA. ZnO shows a well-defined grain structure of variable size in the nanometre range. However, the formation of the 4CPA-ZLH nanohybrid resulted in a flake-like fibrous structure. On heating at 500 ° C for 5 h under atmospheric conditions, the nanohybrid transformed back to a well-defined grain structure, as previously observed with the starting material, ZnO. The release of 4CPA was found to occur in a controlled manner and was generally governed by pseudo-second-order kinetics.